PROFESSIONAL RESPONSIBILITY AND ETHICAL OBLIGATION OF LAWYERS IN A GLOBAL PANDEMIC: CASE STUDY OF COVID-19 PANDEMIC - ISSUES AND CHALLENGES - Kingsley Adeyi Omengala,; Iniye Linda Iyaye Ikimi, (Journal of Legal Studies & Research, 2022)
The world was and is currently overwhelmed by the rabid pandemic known as Coronavirus but coined as COVID-19, which claimed millions of lives. The global impact of COVID-19 pandemic has infiltrated into all sectors of human society; educational, sociological, economic, political, etc. Global affairs were and are still unsettled; so much pressure was mounted on humanity and nations of the world had to adjust their systems in order to cope with the situation. Different professions, particularly the medical profession, had to swiftly adapt to new modes of service delivery. The legal profession and the entire justice delivery sector were not exempted from the profound upshot caused by this pandemic. New methods of rendering legal services had to be adopted to cushion the emasculation of conventional form of service delivery. This paper delves into the professional responsibility and ethical obligations expected of legal professionals in a situation of an outbreak of a global pandemic. It considers the responsibility and ethical obligations from the point of view of both the pandemic era and post-pandemic era, taking the COVID-19 pandemic as a case study. The paper is divided into four parts dealing with introduction, legal profession and professional responsibilities, issues and challenges posed by the pandemic, and lastly, the conclusion. Through the doctrinal methodology, it was discovered that the radical disruption to the legal profession and the court system introduced directly or by necessary implication, emerging issues which the law and the legal profession had to promptly adjust to, in order to keep pace with the new normal.